Non-Neurological Complications after Mechanical Thrombectomy for Acute Ischemic Stroke: A Retrospective Single-Center Study. (23rd December 2022) - Goffin, Pierre; Thouny, Romain; Guntz, Julien; Brisbois, Denis; Desfontaines, Philippe; Demaret, Pierre
Abstract : Introduction . The global burden of stroke is high and mechanical thrombectomy is the cornerstone of the treatment. Incidences of acute non-neurological-complications are poorly described. Improve knowledge about these complications may allow to better prevent, detect and/or manage them. The aim is to identify risk markers of death or poor evolution. Method . We conducted a retrospective single-center study to analyzed the incidence of non-neurologicalcomplications after mechanical thrombectomy in acute ischemic stroke. Patients who had experienced a stroke and undergone thrombectomy were identified using a registry in which we prospectively collected data from each patient admitted to our hospital with a diagnosis of stroke. Quantitative and qualitative variables were analyses. The association between studied variables and hospital death was assessed using simple logistic regression models. Result . 361 patients were reviewed but 16 were excluded due to a lack of medical information. Between 2012 and 2019, 345 patients were included. The median admission NIHSS score was 15. Seven percent of the patients died in the ICU. The following independent risk markers of death in the ICU were identified by logistic regression: respiratory complication, hypotension, infectious complication, and hyperglycemia. Conclusion . In this large retrospective study of stroke, respiratory complications and pulmonary infections represented the most important non-neurological adverse events encountered in the ICU and associated with a risk of death.